El rol de la familia y su incidencia en el comportamiento social de los niños y niñas de preparatoria, primer grado de educación básica de la escuela fiscal mixta Héroes del Cenepa de la ciudad de Loja. Período 2013 – 2014 . Lineamientos alternativos - Tillaguango Pintado, Esther Imelda (2014)
This research entitled: "THE FAMILY ROLE AND ITS IMPACT ON BASIC EDUCATION FIRST GRADE CHILDREN SOCIAL BEHAVIOR OF "“HEROES DEL CENEPA" SCHOOL LOJA.CITY PERIOD 2013 - 2014 ". ALTERNATIVE GUIDELINES. It was structured on the basis of current guidelines Graduation at the Loja National University. The general aim of the research process was guided: Educate parents about the importance of the Role of the Family in the Social Behavior of Children of School, First Grade Basic Education "Heroes del Cenepa " School Loja city. Period 2013-2014. The methods and instruments used were: Scientist, Inductive-Deductive, Descriptive, and Statistical Model. The techniques applied were: Survey applied to parents of children to identify the Role of Family; and, an Observation Guide applied to children of School, First Grade Basic Education "Heroes del Cenepa" School Loja city to determine their Social Behavior. According to the Parents Survey found that: 62% of Respondents Parents who instill values in their children home implement in daily life always; 21% often; and, 17% sometimes. 67% of respondents Parents potentiate individual capacities and abilities of their children forever; 25% often and 8% at times. According to the results of the Observation Form, the following result was obtained: 54% of girls and boys have researched Shy Behaviors and 46% no; 38% have Assertive Behaviors and 62% no; 18% have Passive Behaviors and 82% no; and 12% have Aggressive Behaviors and 88% no.